2019
DOI: 10.1177/0144598719876056
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of the performance of a single-well groundwater source heat pump system in Beijing, China

Abstract: Shallow geothermal energy is stable and clean. Using a heat pump to produce groundwater and realize heating and cooling can effectively prevent haze and reduce energy consumption. To reduce engineering costs, many buildings in Beijing, China, plan to utilize single-well groundwater source heat pumps. Numerical modeling is an effective way to gain an understanding of thermal transport processes. However, wellbore-reservoir coupling and the uncertainty of productivity due to geological parameters make simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The heating area under intermittence operation was 4000 m 2 more than that under continuous operation. Xu et al. (2020a) further simulated the performance of a single-well groundwater source heat pump system in Beijing, China and found that the output temperature for a single well serving an area of 9000 m 2 during the heating season was 11–15°C.…”
Section: Research Topics Investigatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating area under intermittence operation was 4000 m 2 more than that under continuous operation. Xu et al. (2020a) further simulated the performance of a single-well groundwater source heat pump system in Beijing, China and found that the output temperature for a single well serving an area of 9000 m 2 during the heating season was 11–15°C.…”
Section: Research Topics Investigatedmentioning
confidence: 99%
“…The heating area under intermittence operation was 4000 m 2 more than that under continuous operation. Xu et al (2020a) further simulated the performance of a single-well groundwater source heat pump system in Beijing, China and found that the output temperature for a single well serving an area of 9000 m 2 during the heating season was 11-15 C. Solar energy utilization is very important to help reduce the building energy consumption and even achieve net zero energy buildings. Zhou et al (2021) proposed a solar integrated vacuum freeze-dryer and building air conditioning system, where a solar absorption refrigeration system provides cooling to both the building space and the freeze-dryer.…”
Section: Energy Savings Through Renewable Energy Usagementioning
confidence: 99%
“…In Northern China, Ruoxi Yuan et al examined the significance of fluorine indications in the mediumlow temperature convection geothermal system in the northeast of Hebei Province. [5][6][7][8][9] However, few studies have focused on the content of fluoride ions in Beijing and its surrounding areas. This paper takes the underground hot water in Beijing as the research object, aiming to address the problem of high fluorine content in the underground hot water.…”
Section: Introductionmentioning
confidence: 99%
“…The heat is then transported to the evaporator of the water-source heat pump unit and subsequently released to generate high temperature heat for users such as buildings. The HTHP mitigates issues such as frost, which is prevalent in evaporators of conventional air-source heat pump systems, and the constraints of geological conditions present in water-source/geothermal heat pump systems (Kim et al, 2017;Liu et al, 2019aLiu et al, , 2019bWang et al, 2019;Xu et al, 2020). Therefore, HTHPs have attracted significant research attention in recent years.…”
Section: Introductionmentioning
confidence: 99%